Cognitive behavioural therapy with pharmacotherapy for pathological gambling patient: case report - Erkan Kuru; İlker Özdemir; Yasir Şafak; R. Gökçer Tulacı; M. Hakan Türkçapar (Psychiatry and Clinical Psychopharmacology, 2017)
Pathological Gambling (PG) is a persistent, recurrent, problematic gambling behaviour, leading to clinically significant impairment or distress. Literature studies regarding pharmacotherapy for PG treatment are complicated. Successful and promising results have been obtained with Cognitive Behavioural Therapy (CBT) and pharmacotherapy. In the treatment period with CBT, individual model for gambling behaviour was established and focused on automatic thoughts. Cognitive restructuring was performed and behavioural interventions were used. Also, a relapse prevention plan was devised. The treatment period and effect with pharmacotherapy and CBT of a patient suffering from PG and comorbid depression are discussed in this case report.